2011
DOI: 10.1007/s10658-011-9752-z
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 gene, an additional target for discrimination between the potato cyst nematodes, Globodera rostochiensis and G. pallida, and the related species, G. tabacum tabacum

Abstract: The heat-shock gene, Hsp90, was targeted as a new variable genomic region to supplement other DNA-based tests for identification and discrimination of Globodera pallida, G. rostochiensis and G. tabacum tabacum. Populations of the potato cyst nematodes, G. pallida and G. rostochiensis (PCN), originating from Canada, France, Belgium and USA, together with two populations of G. tabacum tabacum from the USA and France were used for the amplification of a fragment of the Hsp90 gene. General and specific primers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Species identification by real-time PCR diagnostics offers much greater potential for high-throughput screening. Several real time PCR assays for the detection of either G. rostochiensis or G. pallida were developed but data are lacking for the evaluation of their performance especially in terms of sensitivity and specificity against a large range of populations (Reid et al 2010;Nakhla et al 2010;Madani et al 2011)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species identification by real-time PCR diagnostics offers much greater potential for high-throughput screening. Several real time PCR assays for the detection of either G. rostochiensis or G. pallida were developed but data are lacking for the evaluation of their performance especially in terms of sensitivity and specificity against a large range of populations (Reid et al 2010;Nakhla et al 2010;Madani et al 2011)…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the molecular identification of G. pallida and G. rostochiensis, existing conventional PCR tools (Fullaondo et al 1999;Bulman & Marshall 1997;Mulholland et al 1996;Skantar et al 2007;Shields et al 1996;Thiery & Mugniéry 1996) often show cross-reactivity with closely related species (G. tabacum and G. mexicana) and an absence of detection in some South American populations (internal document LSV, 2010), which requires first ever to perform a morphological analysis to process detection of these two species. Some real time PCR tools are described in the literature but they have not been tested against other Globodera species such as G. mexicana, G. ellingtonae or the subspecies of G. tabacum, (Nakhla et al 2010, Reid et al 2010, Madani et al 2011, Papayiannis et al 2013.…”
Section: /28mentioning
confidence: 99%
“…Phylogenetic analyses based on ITS and Hsp90 sequences showed that G. ellingtonae fit in a well-supported clade, more closely related to G. rostochiensis and the G. tabacum complex than to G. pallida. The Hsp90 is one additional gene target for the identification and discrimination of G. pallida, G. rostochiensis and G. tabacum (Madani et al, 2011). Those authors considered samples from Canada, USA, France and Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently real‐time PCR assays have been developed and can be used for identification (e.g. Nakhla et al ., ; Madani et al ., ). This type of test can also be used for direct detection of target species without cyst morphological detection (Reid et al ., ).…”
Section: Identificationmentioning
confidence: 97%